Once Overlooked, Now Made Visible: ATL Proteins and DNA Repair - Reißner, Thomas; Schorr, Stephanie; Carell, Thomas (Angewandte Chemie (International ed.), 2009)
Damage report: Alkyltransferase‐like proteins (ATLs) flip DNA lesions out of the DNA duplex but have no catalytic function. They act as recognition proteins that mark DNA lesions and allow repair (see picture; NER=nucleotide excision repair).